Questioning Level for Critical Thinking Development in Classroom Teaching - Yaakub, Norma; Ab. Rashid, Radzuwan; Khairuddin, Zurina; Mohamed, Amaal Fadhlini; Muhammad Nasir, Noormaizatul Akmar (RABBANICA - Journal of Revealed Knowledge, 2021)
This paper aims to provide insights into the trainee teachers’ questioning level in developing critical thinking or Higher-Order Thinking Skills (HOTS) in primary school classrooms. A constructivism-based teaching instruction of critical thinking incorporation pertaining to the cognitive process dimension of the Revised Bloom’s Taxonomy (2001) is an essential requirement in teaching practices. Notwithstanding, investigations into the Institute of Teacher Education trainee teachers’ readiness in incorporating critical thinking in their teaching practices have revealed that the integration of HOTS questioning level is still low. By employing a single case study of three trainee teachers as participants, data was collected using classroom observations and semi-structured interviews. The qualitative data was analysed by employing interpretivist thematic analysis procedures aided by Atlas.ti software. The themes consisting of Higher-Order Thinking Skill (HOTS) and Lower-Order Thinking Skills (LOTS) questions were obtained. This study concludes that the teaching practice of the trainee teachers needs to be improved as LOTS questions were used predominantly compared to the HOTS questions. Most teaching sessions focused only on the acquisition and understanding of the content of the lesson. The findings are discussed under the light of relevant literature and implications are presented for further research and pedagogical guidelines.